Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

Rivers under stress: geochemical changes along a rural–urban gradient during extreme hydrological events (Greve River, Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2026)
Rivers are increasingly exposed to combined anthropogenic and climate-driven pressures, particularly along rural-to-urban gradients where land use, population density, and contaminant sources progressively intensify downstream. In parallel, prolonged droughts followed by intense rainfall events are becoming more frequent, potentially enhancing contaminant accumulation during dry periods and their rapid mobilization during subsequent first-flush events. However, the interactions between these hydrological extremes and spatial anthropogenic gradients in controlling river geochemistry remain insufficiently understood. This study investigates the spatial and seasonal evolution of river chemistry along the Greve River (Tuscany, Italy), a tributary of the Arno River, characterized by a marked rural-to-urban transition, during the exceptional 2022 European drought and subsequent heavy rainfall event. Six sampling campaigns were conducted between May and October 2022, combining high-resolution spatial monitoring with geochemical and isotopic tracers, including total dissolved solids (TDS), nutrients, and trace elements. The results reveal a progressive downstream enrichment in anthropogenic tracers (e.g., NO 3 − and K + , up to 9 mg/L and 6.6 mg/L, respectively) and pronounced evaporative isotope enrichment during the driest months (slope of the evaporation line ~ 4), indicating strong hydrological stress conditions. The first intense rainfall event triggered rapid remobilization of accumulated material and heterogeneous contaminant transport dynamics. Elevated nutrient concentrations (e.g., NH 4 + , up to 1.4 mg/L) in downstream sectors further reflect the combined influence of hydrological stress and urban inputs. These findings demonstrate how climate-driven hydrological extremes can amplify contaminant mobilization along urbanized river continuums. The integration of isotopic and geochemical tracers provides a transferable framework for assessing water-quality vulnerability in river basins increasingly exposed to hydroclimatic instability.

A novel integrated strategy for air quality monitoring in volcanic-hydrothermal, wetland, urban and industrial areas - R. Biagi; A. Randazzo; S. Venturi; F. Capecchiacci; O. Vaselli; F. Tassi (Atmospheric Environment, 2025)

Methane seepage dynamics and ground heating phenomena in the southern Po Valley: the case study of Santa Maria Nuova (Italy) - G. Capelli Ghioldi; G. Tamburello; A. Sciarra; D. Rouwet; T. Ricci; R. Civico; F. Tassi; P. Severi; M. Liuzzo; M. Coltorti; A.L. Rizzo (Applied Geochemistry, 2025)

Traditional and low-cost technical approaches for investigating greenhouse gases and particulate matter distribution along an urban-to-rural transect (Greve River Basin, Central Italy) - M. Ferrari; R. Biagi; S. Venturi; F. Frezzi; F. Tassi (Environmental Geochemistry and Health, 2025)
Human activities, largely tied to fossil fuels and intensive agriculture, emit massive amounts of climate-altering species and harmful pollutants into the atmosphere that affect soil, ecosystems, and water. Air quality monitoring is crucial to minimize harmful effects and protect human and environmental health. The Greve River basin (Tuscany, central Italy) represents an excellent example of an ecosystem affected by various anthropogenic air contaminants. The upstream areas are predominantly rural, while the downstream zones are characterized by urban and industrial development. Air pollutants throughout the basin were measured adopting two strategies: (i) fixed monitoring at five sites using multiparametric stations equipped with low-cost sensors for CO 2 , CH 4 , and PM 2.5 concentrations; (ii) measurements along a transect using a mobile monitoring station equipped with a Picarro G2201- i analyzer for the determination of CO 2 and CH 4 concentrations and 13 C/ 12 C values of the two gases. Results revealed relatively high CO 2 and CH 4 concentrations downstream, mainly due to vehicular traffic based on the isotopic signature. The temporal and spatial distribution of the contaminants mirrored the evolution of the Planetary Boundary Layer, with peak concentrations in the early morning due to stable atmospheric conditions, and contaminant dilution due to air turbulence during the daytime. Particulate (PM 2.5 ) distribution showed a trend similar to gaseous pollutants, being strongly dependent on wind speed and rainfall events. The high spatiotemporal resolution of data acquisition provided by the low-cost stations for air quality measurements represents an important advance for developing monitoring strategies, complementing the traditional instrumentation commonly used by agencies.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Integrated geochemical and microbiological assessments of Astroni lakes reveals Campi Flegrei unrest signatures - F. Tassi; A. Randazzo; S. Venturi; A. Repetto; S. Fazi; S. Amalfitano; L. Vimercati; A. Butturini; S. Caliro; E. Cuoco; A. Santi; F. Capecchiacci; et al. (Journal of Volcanology and Geothermal Research, 2024)

Fluid geochemistry of the Cerro Galán geothermal system (Southern Puna, Argentina): Implications for the geothermal potential of one of the youngest giant calderas in the Andes - A. Chiodi; W. Báez; F. Tassi; E. Bustos; R. Filipovich; J. Murray; A.L. Rizzo; O. Vaselli; G. Giordano; J.G. Viramonte (Journal of Volcanology and Geothermal Research, 2024)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Unpaved road conservation planning at the catchment scale - C. C. Silva; J. P. G. Minella; A. Schlesner; G. H. Merten; C. A. P. Barros; R. Tassi; A. P. B. Dambroz (Environmental Monitoring and Assessment, 2021)

fMRI-Based Effective Connectivity in Surgical Remediable Epilepsies: A Pilot Study - A. E. Vaudano; L. Mirandola; F. Talami; G. Giovannini; G. Monti; P. Riguzzi; L. Volpi; R. Michelucci; F. Bisulli; E. Pasini; P. Tinuper; L. Di Vito; et al. (Brain Topography, 2021)

Evolution of fluid geochemistry at the Turrialba volcano (Costa Rica) from 1998 to 2008 - O. Vaselli; Franco Tassi; E. Duarte; E. Fernandez; R. J. Poreda; A. Delgado Huertas (Bulletin of Volcanology, 2010)

The magmatic- and hydrothermal-dominated fumarolic system at the Active Crater of Lascar volcano, northern Chile - F. Tassi; F. Aguilera; O. Vaselli; E. Medina; D. Tedesco; A. Delgado Huertas; R. Poreda; S. Kojima (Bulletin of Volcanology, 2009)

Fumarolic gases at Mombacho volcano (Nicaragua): presence of magmatic gas species and implications for volcanic surveillance - K. Garofalo; F. Tassi; O. Vaselli; A. Delgado-Huertas; D. Tedesco; M. Frische; T. H. Hansteen; R. J. Poreda; W. Strauch (Bulletin of Volcanology, 2007)

Correlation between serological immune response analyzed by a new ELISA for HPV-16/18 E7 oncoprotein and clinical characteristics of cervical cancer patients - A. Ravaggi; C. Romani; B. Pasinetti; R. A. Tassi; E. Bignotti; E. Bandiera; F. E. Odicino; M. Ragnoli; C. Donzelli; M. Falchetti; S. Calza; A. D. Santin; et al. (Archives of Virology, 2006)

Antiapoptotic role of p38 mitogen activated protein kinase in Jurkat T cells and normal human T lymphocytes treated with 8-methoxypsoralen and ultraviolet-A radiation - A. Cappellini; P. L. Tazzari; I. Mantovani; A. M. Billi; C. Tassi; F. Ricci; R. Conte; A. M. Martelli (Apoptosis, 2005)